Design and development of a new machine tool for continuous friction stir extrusion. (April 2023) - Buffa, Gianluca; Campanella, Davide; Micari, Fabrizio; Fratini, Livan
Abstract: In the present paper the Continuous Friction Stir Extrusion process (CFSE), derived from the already known Friction Stir Extrusion (FSE), is proposed for effective solid-state recycling of metal scraps. A new dedicated machine tool was designed and developed. A Lagrangian implicit thermomechanical numerical model was set up and used to determine the proper ranges of the most relevant process parameters. An effective case study is proposed, involving the actual extrusion of a recycled wire in a continuous way. Metallurgical observations and mechanical characterization tests were carried out on the obtained specimen showing the potential of the process and its industrial feasibility.